Jinjang flowland: a multi phase designed for deepening journey towards nature remedy - Adnan, Nur 'Ezzati; Hj. Baharuddin, Zainul Mukrim (Kulliyah of Architecture & Environmental Design, International Islamic University Malaysia, 2019)
Malaysia has many ex-mining ponds which can be utilised through a sustainable integrated wetland. It can sove current issues of urban stormwater problemS such as flash flood and pollution. Through design, the ponds have potential for an improved water quality while creating valuable wildlife habitat. There is a growing interest in the use of constructed wetlands for treating and recycling wastewater. The design proposal intends to make full utilisation of the benefits of ponds as a functional and ecological urban park .